Douglas E. Trapp letter to Robert K. Myers regarding bird sightings, June 2, 1988 - Trapp, Douglas E.et al (1988)
Field notes contributed by Douglas E. Trapp in a letter to Robert K. Myers with observers Kevin J. Loftus and Timothy Loftus. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1988. Epson - sheet feed/flatbed